THE BEAUTY OF LOMBOK'S IKAT WEAVING IS ABLE TO INVITE THE CHARM OF FOREIGN TOURISTS TO COME TO INDONESIA(RESEARCH ON THE CUSTOMERS OF LOMBOK SONGKET WOVEN CLOTH IN CENTRAL LOMBOK) - R. Adjeng Mariana Febrianti; Rakhi Naufal Chaerulzaman (Jurnal Darma Agung, 2022)
The business world is required to be more creative in facing increasingly fierce competition. With the enactment of the ASEAN Economic Community (AEC), many global competitors have begun to target the Indonesian market. The purpose of this study was to determine the development of songket in Lombok. The research method used is descriptive verification method through hypothesis testing, modeling approach using SEM, with a selected sample of 100 customers. The results of the study reveal that the ability of creativity, innovation that has been passed down from generation to generation, may not necessarily influence buying interest directly because the role of publication is predicted to increase competitiveness with fellow songket weavers. The suggestion proposed is that publications play an important role in the sustainability of SME businesses in supporting creativity and innovation that can foster interest in buying songket pelkangga.